The Role of School Principals in Implementing the Goals of Learning Disabilities Programs from the Point of View of the Teachers of Learning Disabilities In Riyadh City - Al- Salman, Abrar Abdullah; Al- Shiha, Maha Hamad (Journal of Educational and Psychological Sciences, 2019)
The study aims to identify the role of school leaders in applying the objectives of learning disabilities programs from the perspective of the learning disabilities teachers, and followed the descriptive approach using questionnaire as a tool for collecting information. The sample of the study (127) teachers of learning disabilities. The results of the study showed that there is a moderate agreement between the teachers of learning disabilities in the elementary schools on the role of school leaders in applying the objectives of the learning disabilities programs, where the role of the school leader in providing educational services is ranked first, followed by the role of school leaders in activating the work team learning disabilities programs. The third agreement among the sample teachers is the role of school leaders in the discovery of students with learning disabilities. The final agreement is the role of school leaders in awareness of learning disabilities programs as the least role played by the school leader to implement the objectives of learning disabilities programs. The study also showed that there were no statistically significant differences between the average responses of the study members on the total score of the role of the school leaders in applying the objectives of the learning disabilities programs and its subdivisions according to the education office and the number of years of experience. Also, there were statistically significant differences on the overall result of the role of school leaders in the implementation of the objectives of the programs of learning difficulties and its subdivisions according to the variant of the scientific qualification, in favor of the members of the study who have a diploma qualification.
Keywords: school leaders; learning difficulties programs; teachers of learning difficulties